High Dietary Fiber and Antioxidant Cookies with Substituted Parchment and Silver Skin Coffee - Ester Lanywati; Windy Rizkaprilisa; Lusiawati Dewi (Food Science and Technology Journal (Foodscitech), 2023)
High coffee production in Indonesia effected the increase of by-products from the processing of coffee beans. Parchment and silver skin are by-product obtained during the processing of coffee beans. Parchment and silver skin are used as compost, biogas, and has not been widely used as a food ingredient. Both have a high dietary fiber content and antioxidant activity. In this research, we make cookies with parchment and silver skin flour. Parchment and silver skin flour were added with concentrations consist of 0%, 1%, 2.5%, and 5%. Based on organoleptic assay with the parameters of color, aroma, taste, texture and level of preference, the best cookies were the addition of 2.5% parchment flour. These cookies have nutritional that fulfill the quality standards of cookies (SNI -2973-2011), namely 7.76% protein, 20.86% fat and 1.31% ash. In addition, these cookies have a high content of dietary fiber and antioxidants, namely 13.67% and 43.86%. So, these cookies can be a healthy snack option because have high dietary fiber and antioxidant. Keywords: Antioxiant; Coffee By Product; Cookies; Dietary Fiber; Parchment; Silver skin.